2014
DOI: 10.3109/10717544.2013.876561
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of a marker compound, baicalin in KOB extract after oral administration to normal and allergic-induced rats

Abstract: (2014) Comparative pharmacokinetics of a marker compound, baicalin in KOB extract after oral administration to normal and allergic-induced rats, Drug Delivery, 21:6, 453-458, DOI: 10.3109/10717544.2013 Abstract KOB extracts are a polyherbal medicine had been prescribed for the treatment of hyperhydrosis and allergic diseases such as allergic asthma and rhinitis in oriental clinics. Therefore, the pharmacokinetic studies of the KOB extract administered orally to normal rats and rhinitisinduced rats to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In contrast, no pharmacokinetic changes of baicalin were observed in allergy-induced rats [28]. After an oral administration with 1667 mg/kg KOB extract which is a polyherbal medicine for the treatment of hyperhidrosis, containing 100 mg/kg baicalin, to normal and allergy-induced rats, the obtained pharmacokinetic parameters, such as C max and AUC of baicalin, in allergy-induced rats were similar with those in normal rats [28].…”
Section: Role Of Intestinal Microbiota In Pharmacokinetics Of Baicmentioning
confidence: 99%
“…In contrast, no pharmacokinetic changes of baicalin were observed in allergy-induced rats [28]. After an oral administration with 1667 mg/kg KOB extract which is a polyherbal medicine for the treatment of hyperhidrosis, containing 100 mg/kg baicalin, to normal and allergy-induced rats, the obtained pharmacokinetic parameters, such as C max and AUC of baicalin, in allergy-induced rats were similar with those in normal rats [28].…”
Section: Role Of Intestinal Microbiota In Pharmacokinetics Of Baicmentioning
confidence: 99%
“…Baicalin is principally used in Asian countries as a herbal supplement because of its wide variety of health benefits, including anti-neuroinflammatory 3 , anti-cancer 4 and anti-anxiety effects 5 . It can also improve lung function 6 and fertility 7 .The most common mechanism of Baicalin being against pathogenesis is its protective effect by reducing the production of oxidative stress 8 . Interestingly, Qi et al 9 reported that Baicalin could enhance the developmental competence of mouse embryos through suppressing cellular apoptosis and HSP70 expression, and activating DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption and bioavailability of baicalin from herbal extracts was shown to be higher in rats with ulcerative colitis than in otherwise healthy rats [167,190]. In experimentally allergic rats, though, no differences were seen in the pharmacokinetics of baicalin when compared with normal controls [279].…”
Section: Intra-species Differences (Pk Variability)mentioning
confidence: 99%